Corrosion Behavior of Low Carbon Steel Pipe in Condensate Environment - Royani, Ahmad; Prifiharni, Siska; Priyotomo, Gadang; Sundjono, Sundjono (Trends in Sciences, 2022)
Low carbon steel pipe is widely used in various pipeline applications because it has good mechanical properties. The application of low carbon steel developed generally does not involve corrosion resistance. To find out the behavior of low carbon steel pipe in condensate fluids, the immersion test was carried out. The method for the immersion test is the planned-interval test. The corrosion rate of this steel was determined by weight loss, whereas the corrosivity of the condensate fluids was measured by a multimeter Hach HQ40d. The morphology of corrosion products is characterized by using scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and x-ray diffraction (XRD). The result of immersion of low carbon steel pipe in the condensate fluids shows that the liquid corrosivity and corrodibility of low carbon steel pipe tend to decreases with the length of exposure time. The decrease of metal corrodibility is identical to the lower corrosion rate at a longer exposure time due to the layer a corrosion product formed. The corrosion products during immersion tests are uniform with iron oxide in the form of FeO(OH) and Fe2O3.H2O. GRAPHICAL ABSTRACT